Analisis Kemampuan Siswa dalam Menyelesaikan Operasi Hitung Penjumlahan dan Pengurangan Bilangan Bulat - sri mulyani, ni made; suarjana, i made; tanggu renda, ndara (Universitas Pendidikan Ganesha, 2018)
This study aims to describe the abilities and difficulties who experienced by students on solving the problem of addition and reduction of integer class IV. The research was held in XIV group which consist of three elementary schools, which is SD Negeri 1 Tukadmungga, SD Negeri 2 Tukadmungga, and SD Negeri 2 Pemaron. The number of population in Gugus XIV counted 67 students and used sample consist of 34 students or 50% the population joined from SD Negeri 1 Tukadmungga, SD Negeri 2 Tukadmungga, and SD Negeri 2 Pemaron. The data are collected using test methods, interviews, observations, and documentation. The results showed that teacher facilitated learning activities belong to proper kategory. Teachers present the lessons on interesting way so that the learning process is not boring. Discussion methods was used during the learning process to encourage students to ask and discuss so students can share their ideas.. Students experience difficulty solving problems between positive integers and negative integers in story form. Students experience difficulty because students understood the concept of integers contextually yet. It can be solved by using learning media and contextual emphasis on the concept of learning and observing student development using the results of evaluation at the end of class.